DATA OF CLINICAL PRACTICE AS A TOOL FOR CHOICE OF DIRECT ORAL ANTICOAGULANT - D. А. Napalkov; A. A. Sokolova; V. V. Fomin (Рациональная фармакотерапия в кардиологии)
The review actualizes the need to validate data  obtained in randomized clinical trials (RCT) by the results of routine clinical practice (RCP). Definitely, both methods have some disadvantages. Only patients with minimal comorbidity and a number of other restrictions are included into the RCT in accordance with strict procedures and treatment protocol. On the contrary, the analysis of the RCP shows that data  bases  of insurance companies and medical records are associated with less exact information about the patients, heterogeneity of comparison groups might be significant, and end points evaluation can be different. At the same time, if the RCT data are confirmed by the key results of the RCP analysis, it is a strong  evidence of the credibility of information, obtained by the both methods. The analysis of various RCP data bases published over the past 2 years shows that, among all new oral anticoagulants, apixaban is associated with the best adherence to treatment and lowest bleeding incidence in patients with non-valvular atrial fibrillation. These results confirm good safety profile of apixaban which was previously demonstrated in ARISTOTLE trial. On the contrary, rivaroxaban was associated with the most frequent bleeding in long-term use in patients with atrial fibrillation.